2020
DOI: 10.18388/abp.2020_5198
|View full text |Cite
|
Sign up to set email alerts
|

MiR-139-5p alleviates neural cell apoptosis induced by spinal cord injury through targeting TRAF3

Abstract: Spinal cord injury (SCI) is a neurological trauma that causes loss of locomotor function and sensory deficit. Previous studies showed that miRNAs play a crucial role in SCI. This study further evaluated the potential role of miR-139-5p in the neural cell apoptosis after SCI in rats. A rat SCI model was successfully established and miR-139-5p expression level in SCI rats was down-regulated compared to the sham group (sham operation group) determined by qRT-PCR. MiR-139-5p overexpression via administration with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Likewise, in the brain, TRAF3 promotes neuronal cell death partly through TAK1-MKK-JNK activation in both ischemia/reperfusion and subarachnoid hemorrhage injury models [24,28]. Zhang et al also showed that TRAF3 promoted neuronal apoptosis following spinal cord injury via thoracic vertebral contusion; however, whether this was also dependent on TAK1-MKK-JNK activation was not investigated in this study [29]. Here, we show that NR-TRAF3 regulates TLR4-specific immune activation by LPS endotoxin administration.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Likewise, in the brain, TRAF3 promotes neuronal cell death partly through TAK1-MKK-JNK activation in both ischemia/reperfusion and subarachnoid hemorrhage injury models [24,28]. Zhang et al also showed that TRAF3 promoted neuronal apoptosis following spinal cord injury via thoracic vertebral contusion; however, whether this was also dependent on TAK1-MKK-JNK activation was not investigated in this study [29]. Here, we show that NR-TRAF3 regulates TLR4-specific immune activation by LPS endotoxin administration.…”
Section: Discussionmentioning
confidence: 72%
“…Notably, gene and protein databases report high Traf3 expression in the brain and retina [27]. However, studies regarding TRAF3 function in neuronal tissues have only recently begun to be investigated [24,28,29]. Further, to our knowledge, no retinal-specific mouse models have yet been developed and retinal TRAF3 function has not been explored.…”
Section: Introductionmentioning
confidence: 99%
“…20 Moreover, miR-139-5p also repressed the apoptosis and oxidative stress of neurons to alleviate nerve cell injury. 21,22 In PE-related studies, miR-139-5p was discovered to increase trophoblast cell proliferation, invasion and migration, so it might inhibit PE progression. 23,24 Consistent with these results, our results revealed that miR-139-5p mimic promoted trophoblast cell proliferation, invasion and angiogenesis to reverse the regulation of circ_0077109 on trophoblast cell function.…”
Section: Discussionmentioning
confidence: 99%
“…MiR‐139‐5p had been shown to act as a tumor suppressor to restrain cell proliferation and invasion in many cancers, such as lung adenocarcinoma 19 and hepatocellular carcinoma 20 . Moreover, miR‐139‐5p also repressed the apoptosis and oxidative stress of neurons to alleviate nerve cell injury 21,22 . In PE‐related studies, miR‐139‐5p was discovered to increase trophoblast cell proliferation, invasion and migration, so it might inhibit PE progression 23,24 .…”
Section: Discussionmentioning
confidence: 99%